Design of a Computer Code To Evaluate the Influence of the Harmonics in the Electrical Networks - A. Souli; A. Hellal (Institute of Advanced Engineering and Science, 2012)
This paper aims to present the design of a computer code (HPFCODE), forcalculate a power flow and power losses in power systems under theinfluence of harmonics, using the GUI in MATLAB. After described theprogram was run for two networks IEEE 6 nodes and IEEE 14 nodes. Thepower flow by Newton-Raphson method was calculated as the losses ofactive and reactive power in the lines, respectively, where the loads arelinear and nonlinear (Static Var Compensator(SVC), Thyristor controlledReactor(TCR), and Unified Power Flow Controller ((UPFC)), The resultswere almost consistent and show the influence of higher harmonics onpower losses in electrical networks.DOI:http://dx.doi.org/10.11591/ijece.v2i5.1465